The spectrophotometrical analysis of rhododendrol‐induced leucoderma using a novel multispectral camera. (1st August 2016) - Inoue, M.; Kikuchi, K.; Watabe, A.; Yamasaki, K.; Aiba, S.
Summary: Background: Many users in Japan of skin brightening/lightening cosmetics containing rhododendrol (RD) have developed leucoderma. Leucoderma appears on skin areas repeatedly treated with RD‐containing cosmetics. RD‐induced leucoderma (RDIL) presents different degrees of well‐defined hypopigmentation. It is crucial to determine the degree of hypopigmentation to differentiate RDIL from vitiligo vulgaris (VV). Objectives: To quantitatively evaluate hypopigmentation of RDIL lesions and the recovery of pigmentation, and to compare the hypopigmentation with VV and normal skin. Materials and methods: Sixteen cases of RDIL, nine cases of VV and 15 healthy controls were examined using a novel multispectral camera (MSC) that can simultaneously obtain the reflection intensity at 10‐nm wavelength intervals from 400 to 760 nm of the photographed area. ∆Absorbance was calculated by subtracting the log of reflection intensity of the target area from that of a white reflection standard. Results: Most RDIL lesions showed lower ∆Absorbance than healthy skin and higher ∆Absorbance than VV lesions between 400 and 550 nm. Statistical comparison of the maximum ∆Absorbance from 420 to 460 nm (Max∆Absorbance) for VV, RDIL and control skin showed that the Max∆Absorbance of RDIL was significantly higher than that of VV and lower than that of control skin. The comparison of ∆Absorbance of the same sites in RDIL lesions between the initial visit and 6 months later showed significant improvement after 6 months. Conclusions: These studies demonstrated quantitative changes in RDIL and its recovery phase and suggested the utility of a MSC in obtaining objective colour information of skin disorders.